The social inclusion of young people with serious mental illness: A narrative review of the literature and suggested future directions. (January 2019) - Gardner, Andrew; Filia, Kate; Killackey, Eóin; Cotton, Sue
Background: Social inclusion involves objective participatory (e.g. education/employment) and subjective (e.g. sense of belonging/acceptance) elements across multiple domains. It has been associated with enhanced physical and mental wellbeing yet is a novel construct in the empirical literature (i.e. measures have not been sufficiently developed). Aims: Young people with serious mental illness are reported to be socially excluded. It is unclear whether this is reflected in the social inclusion/exclusion literature. The aim of this narrative review is to determine whether such literature permits a comprehensive (i.e. multi-dimensional, objective and subjective) understanding of social inclusion among young people with serious mental illness. Methods: Searches to identify studies related to the social inclusion and/or exclusion of young people with serious mental illness were conducted on 16 February 2016, 24 August 2016, 16 February 2017, 24 August 2017 and 16 February 2018 in PsycINFO, MEDLINE, the Cochrane Library, SCOPUS, Open Grey, Web of Science, Google and Google Scholar. Results: There is a paucity of research in the explicit social inclusion literature involving young people either with or without serious mental illness as participants. Literatures exist in related independent areas of research (e.g. employment, social networks), but such studies employ heterogeneous methodologies. Conclusion: Multi-dimensional measures of social inclusion incorporating objective and subjective indicators must be developed for young people with and without serious mental illness. This will enable the generation of normative and clinical data. Existing evidence for the social exclusion of young people with serious mental illness comes from objective indicators in isolated domains (e.g. unemployment). Subjective indicators continue to be under-researched. The above-described measures must be employed to further understanding of the apparent discrepancies between young people with serious mental illness and those without serious mental illness. This will elucidate the relationships between objective and subjective elements of social inclusion and the relationships between these elements and the psychological distress that young people with serious mental illness often experience. This has implications for intervention.